2021
DOI: 10.1186/s12916-021-01912-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and mortality rates among patients requiring intermediate care: a national cohort study using linked databases

Abstract: Background Adults increasingly live and die with chronic progressive conditions into advanced age. Many live with multimorbidity and an uncertain illness trajectory with points of marked decline, loss of function and increased risk of end of life. Intermediate care units support mainly older adults in transition between hospital and home to regain function and anticipate and plan for end of life. This study examined the patient characteristics and the factors associated with mortality over 1 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…20 It is well documented that number of hospital admissions increase as people near the end of life and this is often used as a measure to identify such people. 7 However, this paper suggests this does not translate to people admitted to an ICC for rehabilitation; the majority of whom (71%) had no prior admissions that year ( Fig. 5 ).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…20 It is well documented that number of hospital admissions increase as people near the end of life and this is often used as a measure to identify such people. 7 However, this paper suggests this does not translate to people admitted to an ICC for rehabilitation; the majority of whom (71%) had no prior admissions that year ( Fig. 5 ).…”
Section: Discussionmentioning
confidence: 85%
“… 5 , 6 A national study of over 76,000 people admitted to an ICC showed 25% died within a year of admission, highlighting the need to integrate end-of-life care planning alongside rehabilitation in this cohort. 7 This compares to a mortality of 38% following admission to an acute geriatric ward. 8 There are a number of tools to aid prognostication 9 , 10 , 11 , 12 , 13 ; and although these all provide evidence-based guidance as to when a person is likely to be in the last months of life, there is no clear guidance as to who should be carrying out these scores, how often and in which environment.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, they experience precipitating factors that contribute significantly to delirium development, like a hip fracture (around 12-51% incident delirium), a stroke (33% incident delirium), a surgery (13-50% incident delirium) or being in the Intensive Care Unit (19-82% incident delirium) 5 . Despite all these risk factors, delirium prevalence in older patients in these settings ranges from 6-40%, according to studies [3][4][5][6][7][8][9] . Despite the increased availability of intermediate care services, which has led to more publications about delirium in these settings, there is still a lack of literature regarding delirium in intermediate care settings, and the evidence available is still very limited.…”
Section: Geriatric Rehabmentioning
confidence: 99%
“…These facilities care for mainly adults aged 80 years and over, with multimorbidity, where uncertainty is inherent, and following an unplanned admission. Over one in four die within a year of their index admission [ 20 ]. These settings are key for older people to support recovery and rehabilitation, and plan for and anticipate nearness of end of life [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%